Peran Kepercayaan Konsumen Memediasi Pengaruh Citra Merek Terhadap Keputusan Pembelian Fashion Uniqlo di Kota Denpasar - Althof Dimas Saputra; I Gst. Ngurah Jaya Agung Widagda K (Lembaga Pengembangan Kinerja Dosen, 2026)
The fashion industry in Indonesia continues to grow in line with changing trends and consumer behavior, particularly in Denpasar as a center of tourism and lifestyle. UNIQLO is one of the global fashion brands present in Indonesia, known for its LifeWear philosophy that emphasizes quality, functionality, and product innovation. This study aims to analyze the effect of brand image on purchase decisions of UNIQLO products, with consumer trust as a mediating variable. The study was conducted on UNIQLO consumers in Denpasar who have made purchases within the past year, with a sample size of 100 respondents. Data were collected through online and offline surveys in September 2025 and analyzed using path analysis, Sobel test, and Variance Accounted For (VAF) test with SPSS. The results indicate that brand image has a positive and significant effect on purchase decisions, consumer trust also positively influences purchase decisions, and consumer trust significantly mediates the effect of brand image on purchase decisions.